The language of dance: A didactic sequence for the creation of a dance workshop in a bilingual environment (2021)
The purpose of this project is to design a didactic sequence for the creation of a bilingual dance workshop for ninth grade students at a public school in Colombia with extracurricular schedules, where participants will practice their English language skills. Additionally, it is proposed to reflect on the impact that the creation of a didactic sequence has on the students of Licenciatura en Bilingüismo con Énfasis en Inglés.In order to achieve the objective, the workshop sessions are planned under the didactic sequence structure, in which the students will teach their classmates a choreography through instructions and orders in English with the objective of improving the students' oral competences, as well as developing their motor skills through dance. Likewise, a journal will be used to collect reflections that evidence the contributions of the creation of a didactic sequence in our professional development. Finally, we will reflect on the creation of the didactic sequence and on the importance of promoting bilingual spaces where meaningful learning is fostered through interesting practices such as dance and at the same time arouse interest in learning a second language.